1960
DOI: 10.1152/ajplegacy.1960.198.4.797
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism in rats with chronic uremia

Abstract: In order to evaluate the effects of the chronic uremic syndrome upon some aspects of carbohydrate metabolism in vivo, determinations of gastric and intestinal glucose absorption, and of hepatic glycogen deposition were made in 39 chronically uremic rats and in 49 litter-mate controls. A surgical method for producing chronic uremia was developed. Rats fasted for 24 hours were given a glucose gavage of standard concentration. Three hours later residual gastric and intestinal glucose content and liver glycogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1962
1962
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…None the less, it seems likely that the delayed immune response to skin homografts in acute uraemia is due principally to a depression of the metabolism of the antibody-forming cells in lymphoid tissue. There are differences of opinion as to whether carbohydrate metabolism is altered in uraemia (Kleeberg and Gitelson, 1956;Boucot, Nurser, and Merrill, 1960;Cummings and Zottu, 1960), and abnormalities of carbohydrate metabolism cannot be excluded as a cause of the impaired immune response in acute experimental uraemia. In this connexion it has been shown that certain adrenal cortical hormones markedly inhibit the glucose oxidation by suspensions of lymph-node cells in vitro (White, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…None the less, it seems likely that the delayed immune response to skin homografts in acute uraemia is due principally to a depression of the metabolism of the antibody-forming cells in lymphoid tissue. There are differences of opinion as to whether carbohydrate metabolism is altered in uraemia (Kleeberg and Gitelson, 1956;Boucot, Nurser, and Merrill, 1960;Cummings and Zottu, 1960), and abnormalities of carbohydrate metabolism cannot be excluded as a cause of the impaired immune response in acute experimental uraemia. In this connexion it has been shown that certain adrenal cortical hormones markedly inhibit the glucose oxidation by suspensions of lymph-node cells in vitro (White, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…No changes in glycogen synthesis or degradation have been reported in a number of studies carried out on liver slices from normal rats incubated with uremic serum [5] or in livers from uremic animals [8,[14][15][16]. However.…”
Section: G Lycogen M Etabolismmentioning
confidence: 99%